Single-molecule magnet properties of a monometallic dysprosium pentalene complex. Issue 51 (7th June 2018) - Kilpatrick, Alexander F. R.; Guo, Fu-Sheng; Day, Benjamin M.; Mansikkamäki, Akseli; Layfield, Richard A.; Cloke, F. Geoffrey N.
Abstract : The pentalene-ligated dysprosium complex [(η 8 -Pn † )Dy(Cp*)] (1Dy ) (Pn † = [1, 4-( i Pr3 Si)2 C8 H4 ] 2− ) and its magnetically dilute analogue are single-molecule magnets, with energy barriers of 245 cm −1 . Abstract : The pentalene-ligated dysprosium complex [(η 8 -Pn † )Dy(Cp*)] (1Dy ) (Pn † = [1, 4-( i Pr3 Si)2 C8 H4 ] 2− ) and its magnetically dilute analogue are single-molecule magnets, with energy barriers of 245 cm −1 . Whilst the [Cp*] − ligand in1Dy provides a strong axial crystal field, the overall axiality of this system is attenuated by the unusual folded structure of the [Pn † ] 2− ligand.